2020
DOI: 10.1002/lary.29117
|View full text |Cite
|
Sign up to set email alerts
|

National Analysis of 30‐Day Readmission Following Inpatient Sinus Surgery for Chronic Rhinosinusitis

Abstract: Objectives To characterize the incidence, causes, risk factors, and costs of 30‐day readmission after inpatient functional endoscopic sinus surgery (FESS) for patients with chronic rhinosinusitis. Study Design Retrospective cohort study. Methods The Nationwide Readmissions Database was used to characterize readmission after inpatient sinus surgery for chronic rhinosinusitis from 2015 to 2017. International Classification of Disease codes were used to identify the patient population, which included 5,644 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…19 However, despite what these studies may suggest a priori, we find no evidence of increased infectious burden for the diabetic patient. Given that reinfection after surgery has been shown to be a significant predictor of readmission risk, 7 these results are doubly reassuring. Further investigation is needed to determine whether the long-term outcomes begin to diverge between the DM and non-DM patient populations.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…19 However, despite what these studies may suggest a priori, we find no evidence of increased infectious burden for the diabetic patient. Given that reinfection after surgery has been shown to be a significant predictor of readmission risk, 7 these results are doubly reassuring. Further investigation is needed to determine whether the long-term outcomes begin to diverge between the DM and non-DM patient populations.…”
Section: Discussionmentioning
confidence: 95%
“…Postoperative complications are rare after ESS but an analysis of the National Readmissions Database found that up to 11.6% of patients were readmitted at an average cost of $27 141 per patient. 7 A recent investigation of the relationship between DM and immediate postoperative outcomes (<30 days) found an increased risk for reintubation, pneumonia, and urinary tract infection but no difference in readmission or mortality. 8 Further, DM patients have been found to be at increased risk for gram-negative infection of the paranasal sinuses, 9 although no relationship has been established between DM and increased antibiotic use.…”
Section: Introductionmentioning
confidence: 98%
“…This finding has been previously noted for inpatient FESS and can likely be attributed to reduced resources, less support for managing postoperative complications, and more challenge with returning for follow-up and primary care services. 6,15 Previous studies that examined the trends in readmission rates for the conditions targeted by the HRRP have found a significant decline in readmissions for Medicare and Medicaid patients. 16 Despite these trends, the results of our study suggest that disparity by insurance status persists for ER visits.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Subsequent studies that examined the risk factors for hospital readmission after FESS were limited to the inpatient population, predominantly in tertiary academic medical centers, and included heterogeneous patient populations that encompassed CRS and sinonasal tumors. 5,6 Moreover, the demographic and clinical profile of inpatient FESS is likely different from that of ambulatory sinus procedures with a greater burden of comorbidities among the inpatient population. 6 ER visits after outpatient procedures also may not necessarily lead to hospital readmission but can still create tremendous inconvenience and financial hardships for the patients and the facilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation